The Relationship of The Role of The Extension Worker Based On Gender With The Success Level Of The Farmer Group In Taliwang District, West Sumbawa Regency - Hayati, Hayati; Muktasam, Muktasam; Supartiningsih, Sri (Universitas Mataram, 2024)
This study aims to analyze the role of extension workers based on gender, the level of success of farmer groups in this case in behavior change, and the relationship between the role of extension workers and changes in the behavior of farmer groups. The research was conducted in Taliwang District using survey techniques. Structured interviews were conducted with 48 farmer respondents and in-depth interviews with extension workers. The data were analyzed using descriptive statistics, different test statistics, and Spearman's rank correlation. Research has found that female extension workers have a higher role than men, the level of behavior change in members of the farmer groups assisted by female extension workers is higher than in male extension workers. however, there is a correlation between the roles of both male and female extension workers with an increase in changes in the behavior of farmer group members. Thus, both female and male extension workers have the same potential to change farmer behavior. It is hoped that male extension workers can take the same approach as female extension workers, namely conducting coaching to the farmer groups under their supervision very intensively and using methods appropriate to the group's characteristics.